Evaluate the Implementation of Patient Safety Standards in Baharloo Hospital - Farin Razaghi Kashani; Masoumeh Kazemi Torki (Patient Safety and Quality Improvement Journal)
Introduction:The aim is to conduct an initial evaluation of Baharloo Hospital to assess its adherence to patient safety standards, laying the groundwork for the adoption of the WHO/EMRO Patient Safety Friendly Hospital Initiative (PSFHI). The overarching objective is to elevate the standard of patient safety and foster a culture of safety among both hospital staff and patients.Materials and Methods: The evaluation process utilized the PSFHI assessment manual, which includes a comprehensive collection of critical, core, and developmental standards. Three primary review tools were employed for the assessment: document review, face-to-face interviews, and observation.Results: The leadership and management domain exhibited the highest scores in critical criteria, reaching 89%, while the safe evidence-based clinical practice measures domain followed closely with 58%. The hospital demonstrated implementation of the majority (71%) of critical standards, over half (60.5%) of the core standards, and more than a quarter (28%) of the developmental standards.Conclusions: The baseline assessment reveals that Baharloo Hospital exhibited partial adherence to the patient safety standards mandated by the PSFHI. There exists an opportunity for enhancement to ensure the fulfillment of 100% of critical requirements, a fundamental prerequisite for achieving the status of a Patient Safety Friendly Hospital.